Easy cleaning broom / Dhiya Afkar Zainuddin ...[et al.] - Zainuddin, Dhiya Afkar; Azmi, Mohamad Hadis; Abd Shukor, Mohamad Iqbal Hakkiemi; Mazlan, Ilman Hakim; Nazarulasmal, Alif; Ungku Sallehudin, Ungku Aishah Nabila
Cleaning is a daily basis that is very important in every household. When it comes to cleaning, a lot of people would rant on it, taking it as a burden but it is a necessary part of daily life that should be done in order to keep the living environment remain clean, organized free from bad germs thereby promoting good health to the people surrounding. (Deshpande, 2018) Sayee Deshpande, a psychologist stated that cleaning could help you to have the sense of responsibility and can be a part of preparation for employment. Is it because, doing chores will basically make people learn how to carry out tasks and get them done within the time given. Hence, easy cleaning is created to ease people’s work in doing chores. This project is carried in order to help people do their daily house chores without feeling burdened by it. This project also targeted bottom and middle classes people to afford cleaning equipment that is very convenient and can be used in a long period of time. Since this product is focusing on cleaning scope, of course it is open to every housewives of house husbands, bachelors and also students who are currently living away from their family. This project is expected to help people reduce their time spending on doing chores so they can focus more on their daily basis.